Electricity generation potential from biogas produced from organic waste in Mexico. (February 2016) - Rios, Mario; Kaltschmitt, Martin
Abstract: The provision of biogas from organic residues and wastes as well as its use as a renewable source of energy for electricity generation could contribute to a more environmental sound energy supply. Thus, this paper presents a methodology to estimate the theoretical, the technical and the economic potential of electricity generation from biogas of various organic waste sources. Additionally, it includes an assessment of the uncertainties aligned with such potential assessments. The outlined methodological approach comprises a bottom-up resource focused procedure with statistical and spatial analysis for selected organic waste sources. This allows the identification of municipalities/regions where electricity generation from organic waste via the biogas route is most promising. The method is exemplary demonstrated for the given situation in Mexico. The gathered results show that the methodological approach directs to plausible results. These results show also that Mexico has a considerable potential to use biogas from organic residues as a renewable source for electricity generation. Results indicate an average theoretical potential of roughly 167.9 TWh/a (143.5–192.3 TWh/a), a technical potential of circa 10.2 TWh/a (3.6–23.8 TWh/a) and an economic potential of approximately 6.4 TWh/a (2.0–15.2 TWh/a). This later economic potential could be located in around 391 municipalities in Mexico. The methodology proposed here may hold true for other countries with similar conditions and considerable lack of primary data.